HYDRODYNAMIC VOLTAMMETRY WITH MICROELECTRODES - CHANNEL MICROBAND ELECTRODES - THEORY AND EXPERIMENT - Compton, R; Fisher, A; Wellington, R; Dobson, P; Leigh, P (1993)
Theory is reported that predicts the mass-transport limited current flowing at a microband electrode located in a rectangular channel through which solution is pumped under laminar flow conditions. The effect of electrode size and solution flow rate is quantified and the relative roles of axial diffusion and convective mass transport are identified. Theory is found to be in excellent agreement with experiments conducted on the reduction of p-chloranil and the oxidation of ferrocene by using gold channel microband electrodes. © 1993 American Chemical Society.